SOLID POTENTIAL IN DECANTER DEVICES IN PALM OIL MILLS WITH DIFFERENT FRESH FRUIT BUNCH PROCESSING CAPACITIES AS A SUPPLIER OF NUTRIENTS IN OIL PALM PLANTATIONS - Zain Arrasyid Munthe,; Rangkuti, Ika Ucha Pradifta (Jurnal Silva Samalas, 2026)
This study aims to analyze the potential of solids from decanter mills (PKS) with capacities of 30 tons/hour and 60 tons/hour as a nutrient source for oil palm plants. This research is part of the final assignment for the Plantation Product Processing Technology Study Program at the Indonesian Palm Oil Institute (IPT) and was conducted under the guidance of Ika Ucha Pradifta Rangkuti. The research method used was descriptive quantitative through laboratory analysis of the macro- and micronutrient content in the solids from decanters. Samples were taken from the decanter output of each PKS and then analyzed for Nitrogen (N), Phosphorus (P), Potassium (K), Magnesium (Mg), Calcium (Ca), and micronutrients such as Iron (Fe), Manganese (Mn), Zinc (Zn), Copper (Cu), and Boron (B). The analysis data were analyzed using an Independent T-Test to determine differences in nutrient content between the two PKS capacities. The results of the study showed that the solids from both PKS contain complete macro and micro nutrients so they have the potential to be used as organic fertilizer in oil palm plantations. Solids from the PKS with a capacity of 30 tons/hour have higher contents of Potassium (K), Magnesium (Mg), Calcium (Ca), Iron (Fe), and Manganese (Mn) so they better support the generative phase of plants, while solids from the PKS with a capacity of 60 tons/hour have higher Nitrogen (N) content so they are more suitable for supporting the vegetative phase. Solid production also increased with increasing plant capacity, namely by 4.35 tons/hour in the PKS with a capacity of 30 tons/hour and 8.70 tons/hour in the PKS with a capacity of 60 tons/hour. The results of statistical tests showed that all nutrient parameters were significantly different (p < 0.05), which indicates that plant capacity has a significant effect on the quality of the solid nutrients produced. Keywords: solid palm oil, macro and micro nutrients, decanter, organic fertilizer, PKS 30 tons/hour, PKS 60 tons/hour.